The Impacts of Legacy Mining Operation on Inorganic Arsenic Bioaccumulation and Exposure in Yellowknife, Northwest Territories, Canada - Tanamal, Claudia (Université d'Ottawa / University of Ottawa, 2019)
Arsenic transfers and toxicology are important topics of research and a public health concern because arsenicosis affects millions of people worldwide every year. One of the most significant sources of arsenic in the environment is industrial wastes, such as by-products of mining operation. In Yellowknife, Northwest Territories, Canada, there were two large gold mines—Giant Mine and Con Mine, along with dozens of small-scale mines. The combined by-product of emission from these roasters might have contributed to high concentrations of arsenic found in the city. This thesis presents the results of two related studies to address the environmental health concern: (1) to investigate the arsenic transfers and arsenic species accumulation in freshwater food webs near large legacy mining operations in Yellowknife, and (2) to assess the long-term health risk of inorganic arsenic exposure from the consumption of fish in Yellowknife among the general residents and the Yellowknives Dene First Nation. We found that inorganic arsenic is biominified in food webs (i.e. inorganic arsenic concentrations diminish at higher trophic positions relative to lower trophic positions). Higher-trophic organisms have low inorganic arsenic concentrations in tissue due to biotransformation of inorganic arsenic to non-toxic organic arsenobetaine, and effective elimination of arsenic from their tissue. The trophic positions of freshwater organisms can be used to predict the range of arsenic concentrations and its species composition, accounting for more than 80% of variance. Dietary study results show that the Yellowknives Dene First Nation consumed significantly more fish in their diets (adults: 19 g/day, children: 9 g/day) compared to the general residents of Yellowknife (adults: 9 g/day, children: 5 g/day). Our probabilistic risk assessments showed no significant long-term non-carcinogenic and carcinogenic health risks of inorganic arsenic exposure from fish consumption for the majority of Yellowknife residents, but elevated cancer risks among the adult heavy fish consumers in Yellowknife. However, our data suggested that the residents of Yellowknife were not exposed to higher cancer risks from inorganic exposure compared to the general population in Canada. Therefore, due to fish health benefits and the values associated with its consumption, fish should continue to be a major source of sustenance in Yellowknife.
Keywords: Arsenic speciation; Food webs; Mining; Probabilistic risk assessment; Bioaccumulation; Arsenic dynamics